Emergency Airway Management: A Look into the Practice, Rate of Success, and Adverse Events of 94 Endotracheal Intubations - Fadhlillah, Fiqry (J Emerg Trauma Shock, 2020)
CONTEXT: Endotracheal intubation in the critically unwell is a life-saving procedure, frequently performed in the emergency department (ED). The 4(th) National Audit Project (NAP4) of the Royal College of Anaesthetists and Difficult Airway Society, however, highlighted the deficiencies that could have led to serious harm. In direct response to NAP4, a 2018 guideline was published on the management of intubations in critically ill adults. AIMS: This study describes the current practice of endotracheal intubation, in comparison to the published 2018 guideline. SETTINGS AND DESIGN: A retrospective observational study in an ED of a district general hospital in Greater London. SUBJECTS AND METHODS: Adult attendances from September 1, 2017, to September 1, 2018 (>18 years old) fulfilling the search criteria were reviewed, producing 1553 case notes. These cases were individually reviewed by the authors. STATISTICAL ANALYSIS USED: Mann–Whitney U-test. RESULTS: There were 94 intubations, male to female ratio 1.8:1. The most common indication was for airway protection (n = 35), followed by respiratory failure (n = 23). There were 31 first-pass intubation successes. Intensivists performed most of the intubations (n = 66), followed by anesthetists (n = 13), and ED physicians (n = 10), but with no significant difference between the response rates of ED and external physicians (P = 0.0477). Propofol was the induction drug of choice (n = 37), with rocuronium the paralyzing agent of choice (n = 42). Altogether, there were eight complications reported. CONCLUSIONS: This study provides an overview of the intubation practices in a single-center ED. Non-ED physicians perform the majority of intubations, with a variety of induction and paralyzing agents being used. It adds to the growing call for better standardization and provision of care to patients with a deteriorating airway and the continued auditing of practice.